Stratospheric Aerosol and Ozone Responses to the Hunga Tonga‐Hunga Ha'apai Volcanic Eruption. Issue 4 (15th February 2023) - Lu, Jinpeng; Lou, Sijia; Huang, Xin; Xue, Lian; Ding, Ke; Liu, Tengyu; Ma, Yue; Wang, Wuke; Ding, Aijun
Abstract: The Hunga Tonga‐Hunga Ha'apai (HTHH) eruption on 15 January 2022 was one of the most explosive volcanic events of the 21st century so far. According to satellite‐based measurements, 0.4 Tg of sulfur dioxide (SO2 ) was injected into the stratosphere during the eruption. By using observations and model simulations, here we investigate changes in the chemical compositions of the stratosphere 1 year after the HTHH eruption and examine the key physical and chemical processes that influence the ozone (O3 ) concentrations. Injected SO2 was oxidized into sulfate during the first 2 months, and transported from the tropics to the Antarctic by the Brewer‐Dobson circulation within 1 year. In mid‐to‐low latitudes, enhanced sulfate aerosol increased O3 concentrations in the middle stratosphere but declined in the lower stratosphere. In addition to the chemical processes, sulfate aerosols also reduced polar low‐stratospheric O3 concentrations through enhanced Antarctic upwelling anomalies. Plain Language Summary: The Hunga Tonga‐Hunga Ha'apai (HTHH) eruption on 15 January 2022 was one of the most explosive volcanic eruptions of the 21st century and has attracted global attention. Volcanic ash and gases entering the atmosphere could affect weather and climate processes. Recent studies have largely explored the effects on global warming of HTHH eruption, and have founded that its climate impact is not very strong. However, its impacts on ozone (O3 ) remains unclear. We used observations and models to analyze how HTHH eruption could influence O3 . It confirms that stratospheric O3 can be affected when volcano‐induced aerosols are transported. We suggest that physical and chemical processes combine together to influence stratospheric O3 after HTHH eruption. Moreover, the effect on O3 of HTHH eruption is probably one of the reasons for the recent discovery of a larger O3 hole in Antarctica. Key Points: Volcano‐induced stratospheric sulfate aerosols are transported toward the South Pole and downwards by the Brewer‐Dobson circulation Catalytic nitrogen oxide ozone loss cycles and sulfate aerosols' radiative effects cause extra‐polar stratospheric ozone anomalies Volcanic aerosol‐induced heterogeneous chemistry and enhanced upward transport causes polar stratospheric ozone anomalies